Aus philosophischen Problemen der Phonologie - Bańczerowski, Jerzy (Studia Germanica Posnaniensia, 2018)
Phonology as a linguistic subdiscipline cannot dispense with a philosophical foundation, which in fact should underlie any theoretical activity in this field. The philosophy of phonology includes epistemological, methodological and ontological considerations. The discussion of epistemological problems in this paper touches upon the criteria, sources and limits of cognition as well as on the relation between subject and object of cognition. The exploration of methods of formulation and substantiation of phonological theories is proposed as the main task of the methodology of phonology. In the chapter devoted to the ontology of phonology the entities of phonological domain and their properties are dealt with. Also attention is drawn to the dualities inhering within the phonological reality.